Using satellite images to asses the effect of road lighting on the number of road accidents - Furlanetto, Luca; Janstrup, Kira Hyldekær; Rasmussen, Thomas Kjær (Proceedings from the Annual Transport Conference at Aalborg University, 2019)
Traffic safety represents an important research topic in transportation. The correlation between the risk of accident and road lighting is well known in literature. For example, Per Ole Wanvik estimated that on average the reduction of injury accident during darkness is around 30% in areas with road lighting. Some other studies analyzed the influence of road lighting on traffic safety on highways or in intersections. A common approach in such evaluations is to compare the number of accidents occurring in the daytime with the ones occurring in the nighttime. The presented work is not limited to a particular road type and consider most of the roads in Denmark. The analysis is based on a comparison of the number of nighttime accidents occurring in roads with different light intensity levels, accounting also for road type and flow. Moreover, this study introduces a new method to evaluate the intensity of road lighting throughout the use of satellite images. In literature, the use of satellite image in traffic safety is limited on analyzing road design or traffic volume.